Mediation of legitimacy in early China : a study of the neglected Zhou scriptures and the Grand Duke traditions - Grebnyev, Georgiy, 1983- (Columbia University Press, 2022)
"Scholarship on early China has traditionally focused on a core group of canonical texts. However, understudied sources have the potential to shift perspectives on fundamental aspects of Chinese intellectual, religious, and political history. Yegor Grebnev examines crucial noncanonical texts preserved in the Yi Zhou shu (Neglected Zhou Scriptures) and the Grand Duke traditions, which represent scriptural traditions influential during the Warring States period but sidelined in later history. He develops an innovative framework for the study and interpretation of these texts, focusing on their role in the mediation of royal legitimacy and their formative impact on early Daoism. Grebnev demonstrates the centrality of the Yi Zhou shu in Chinese intellectual history by highlighting its simultaneous connections to canonical traditions and esoteric Daoism. He demonstrates that the Daoist rituals of textual transmission embedded in the Grand Duke traditions bear an imprint of the courtly environment of the Warring States period, where early Daoists strove for prestige and power, offering legitimacy through texts ascribed to the mythical sage rulers. These rituals appear to have emerged at the same period as the core Daoist philosophical texts and not several centuries later as conventionally believed, which calls for a reassessment of the history of Daoism's interrelated religious and philosophical strands. Offering a far-reaching reconsideration of early Chinese intellectual and religious history, Mediation of Legitimacy in Early China sheds new light on the foundations of the Chinese textual tradition"-- Provided by publisher
Keywords: Yi Zhou shu.; Yi Zhou shu -- Criticism, Textual.; Yi Zhou shu; Transmission of texts -- China -- History -- To 1500.; Taoism -- China -- History -- To 1500.; Legitimacy of governments -- Religious aspects -- Taoism.; China -- History -- Zhou dynasty, 1122-221 B.C. -- Historiography.; China -- Intellectual life -- To 221 B.C.; Chine -- Histoire -- 1122-221 av. J.-C. (Dynastie des Zhou) -- Historiographie.; Chine -- Vie intellectuelle -- Jusqu'à 221 av. J.-C.; HISTORY -- Asia -- China.; Historiography; Intellectual life; Taoism; Transmission of texts; China; To 1500; Criticism, interpretation, etc.; History